Mathematical biology. I, An introduction - Murray, J. D. (James Dickson), 1931- (New York, NY : Springer New York, 2002)
It has been over a decade since the release of the now classic original edition of Murray's Mathematical Biology. Since then mathematical biology has grown at an astonishing rate and is well established as a distinct discipline. Mathematical modeling is now being applied in every major discipline in the biomedical sciences. Though the field has become increasingly large and specialized, this book remains important as a text that introduces some of the exciting problems that arise in biology and gives some indication of the wide spectrum of questions that modeling can address. Due to the tremendous development in the field this book is being published in two volumes. This first volume is an introduction to the field, the mathematics mainly involves ordinary differential equations that are suitable for undergraduate and graduate courses at different levels. For this new edition Murray is covering certain items in depth, giving new applications such as modeling marital interactions and temperature dependence sex determination. SIAM, 2004: "Murray's Mathematical Biology is a classic that belongs on the shelf of any serious student or researcher in the field. Together the two volumes contain well over 1000 references, a rich source of material, together with an excellent index to help readers quickly find key words. ... I recommend the new and expanded third edition to any serious young student interested in mathematical biology who already has a solid basis in applied mathematics.".
Continuous Population Models for Single Species -- Discrete Population Models for a Single Species -- Models for Interacting Populations -- Temperature-Dependent Sex Determination (TSD): Crocodilian Survivorship -- Modelling the Dynamics of Marital Interaction: Divorce Prediction and Marriage Repair -- Reaction Kinetics -- Biological Oscillators and Switches -- BZ Oscillating Reactions -- Perturbed and Coupled Oscillators and Black Holes -- Dynamics of Infectious Diseases: Epidemic Models and AIDS -- Reaction Diffusion, Chemotaxis, and Nonlocal Mechanisms -- Oscillator-Generated Wave Phenomena and Central Pattern Generators -- Biological Waves: Single-Species Models -- Use and Abuse of Fractals.
Elektronická reprodukce.
Keywords: matematická biologie; aplikovaná matematika; biofyzika; mathematical biology; applied mathematics; biophysics; e-knihy online; e-books online